2017
DOI: 10.3233/cbm-160528
|View full text |Cite
|
Sign up to set email alerts
|

The value of contrast-enhanced computed tomography in predicting gastric cancer recurrence and metastasis

Abstract: Our study suggests that CECT has a high accuracy rate for predicting postoperative GC recurrence and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A study published in 2017 demonstrated that the maximum HU value represents the highest degree of tumor enhancement reflecting the more aggressive tumors [28]. In another study that investigated the predictive value of CT at diagnosis for early recurrence and metastasis in GC patients, it was found that compared with patients without recurrence and metastasis, those with recurrence and metastasis demonstrated higher CT values in the arterial and venous phases [29]. Both higher T stage accuracy, predictive, and prognostic importance of CT attenuation in GC patients may be related to increased neovascularization [30].…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2017 demonstrated that the maximum HU value represents the highest degree of tumor enhancement reflecting the more aggressive tumors [28]. In another study that investigated the predictive value of CT at diagnosis for early recurrence and metastasis in GC patients, it was found that compared with patients without recurrence and metastasis, those with recurrence and metastasis demonstrated higher CT values in the arterial and venous phases [29]. Both higher T stage accuracy, predictive, and prognostic importance of CT attenuation in GC patients may be related to increased neovascularization [30].…”
Section: Discussionmentioning
confidence: 99%
“…[5] In addition, contrast-enhanced computed tomography (CT) was the most commonly used imaging method to detect recurrence of gastric cancer, with a sensitivity of only 70%-73%. [6] Therefore, there is an urgent need for highly accurate biomarkers to detect recurrence of gastric cancer in clinical practice so that patients with recurrence can receive timely treatment and ultimately improve their survival. [7,8] Circulating tumor DNA (ctDNA) is a fragment of DNA that is released into the bloodstream when a tumor undergoes necrosis or apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence of GC is decreasing by nearly 2% per year worldwide, the overall treatment effect has not fundamentally improved due to population growth [3]. The highly invasive behavior of GCs often leads to recurrence and metastasis, which are the main causes of death in patients [4]. GC-related genes, including oncogenes and tumor suppressor genes, are closely related to the malignant biological behavior of GC [5].…”
Section: Introductionmentioning
confidence: 99%